Rifampicin Induced Acute Interstitial Nephritis in a Patient with Tubercular Lymphadenitis: A Case Report (BIRDEM Medical Journal, 2018)
Rifampicin is one of the most effective anti-tubercular agents. Among its rare adverse effects, acute interstitial nephritis (AIN) is noteworthy. Here, we describe the case history of a 55-year-old female with tubercular lymphadenitis who developed rifampicin induced AIN upon re-exposure and recovered satisfactorily without requiring steroids. Rifampicin induced AIN should be kept in mind when patients present with acute kidney injury as prompt diagnosis and discontinuation of the drug has excellent prognosis.Birdem Med J 2018; 8(3): 257-259